Improving nutrition as a development priority: Addressing undernutrition in national policy processes in Sub-Saharan Africa - Benson, Todd (International Food Policy Research Institute, 2008)
Undernutrition remains a major source of human suffering and an obstacle to national economic and human development in many African countries. This report investigates undernutrition's persistence, drawing on case studies of the public response to the problem in Ghana, Mozambique, Nigeria, and Uganda. Analyzing each nation's policymaking structures, political actors, understanding of undernutrition, and the timing of public responses, the author explains why none of these four nations has mounted an effective campaign to eliminate undernutrition. The author identifes several different causes of this shortcoming, with one underlying flaw in the various public responses standing out: a fundamental failure on the part of political leaders to see undernutrition as a grave problem that undermines development efforts in their nations. The author concludes that an effective response to undernutrition in these countries requires the formation of national advocacy coalitions that can raise public awareness of the problem, highlight policymakers' duty to ensure the nutrition of their citizens, and link proper nutrition to general national development. This report should serve as a resource for advocates, researchers, and others concerned with undernutrition in Africa.